2006
DOI: 10.1063/1.2364449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light irradiation on the characteristics of organic field-effect transistors

Abstract: Highly sensitive thin-film organic phototransistors: Effect of wavelength of light source on device performance J. Appl. Phys. 98, 074505 (2005); 10.1063/1.2061892High-photosensitivity p -channel organic phototransistors based on a biphenyl end-capped fused bithiophene oligomer Appl. Phys. Lett. 86, 043501 (2005);The effect of light irradiation on the characteristics of organic field-effect transistors containing sexithiophene ͑6-T͒ and pentacene was examined. Organic phototransistors ͑OPTs͒ in which 6-T and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
48
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 48 publications
4
48
0
Order By: Relevance
“…Photoresponsivity ͑R ph ͒ is estimated using R ph = I ph /͑E·W·L͒, where I ph is the photoinduced excess drain current and E is incident light intensity ͑W/cm 2 ͒. 8 When the gate bias increases, R ph is enlarged. This is known as the photofield effect, when electron-hole pairs generated in the band-bending region are swept away by the electric field ͑from applied gate voltage V G and drain voltage V D ͒.…”
Section: Resultsmentioning
confidence: 99%
“…Photoresponsivity ͑R ph ͒ is estimated using R ph = I ph /͑E·W·L͒, where I ph is the photoinduced excess drain current and E is incident light intensity ͑W/cm 2 ͒. 8 When the gate bias increases, R ph is enlarged. This is known as the photofield effect, when electron-hole pairs generated in the band-bending region are swept away by the electric field ͑from applied gate voltage V G and drain voltage V D ͒.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Since most organic materials applied in thin-film transistor devices are based on extended p-conjugated systems the absorption of visible light and the resulting photoconductive and photovoltaic effects may cause a strong impact on the device characteristics. 5,6 The understanding and the control of these effects are essential in order to prevent malfunction of the devices in ambient light. On the other hand, taking advantage of these features enables the realization of photosensitive transistors that can be used, e.g., for light detection and light induced switches.…”
mentioning
confidence: 99%
“…On the other hand, taking advantage of these features enables the realization of photosensitive transistors that can be used, e.g., for light detection and light induced switches. [6][7][8][9][10][11][12] Among the different approaches to fabricate organic thinfilm transistors, the use of self-assembled monolayers as part of a thin hybrid dielectric has proven to be a promising route to realize flexible, low-power consuming organic thin-film transistors and circuits with a promising stability. 13,14 Moreover, it has been shown that applying molecules with electron acceptor functionality in a self-assembled monolayer (SAM) on a thick SiO 2 dielectric leads to a large photosensitivity in combination with pentacene as the semiconductor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported a light response of organic thin films. 2,9,10,[34][35][36][37][38][39][40][41] Here, we show via SKPM that when the OTFT is illuminated with white light during the application of bias stress, the amount of trapped charge is diminished (Figure 3(a), (c)). An associated increase in I SD is also observed when the OTFT is illuminated (150 s after device is turned "ON").…”
mentioning
confidence: 99%